KAJIAN MONUMEN PATUNG PERJUANGAN NANI WARTABONE MELALUI VISUALISAI DAN LATAR BELAKANGNYA - Muhammad Isla (Universitas Komputer Indonesia, 2019)
This study aims to find out how to study the Nani Wartabone statue in terms of visuals, to provide knowledge to the people of Gorontalo the meaning of the Nani Wartabone statue and to describe the background study and visualization of the Tilongolo Nani Wartabone monument statue. This research was written using descriptive qualitative research methods, the authors observed in detail the background and visualization of the Tilongolo Nani Wartabone monument, the results of this study allow the writer to know the historical background of the Tilongolo Nani Wartabone monument statue and the writer can also know the visual meaning of the Tilongolo Monument statue Nani Wartabone. The research results obtained by the author are quite good because there are two sources who are quite helpful in the process of writing this research, the conclusion or the final result of this study is that the writer and the public can find out the background of the Nani Wartabone statue made to commemorate his services in fighting the invaders and the meaning of the visualization of the statue of the struggle of Nani Wartabone, namely: (1) The pointing hand has a meaning, namely his birthplace, Bube Village, Suwawa District, Bone Bolango Regency, Gorontalo Province; (2) Bayonet in the left pocket is made by Suwawa which has the mystical power to protect Nani Wartabone in certain situations; (3) The pistol in the right pocket is used as a helper for the main weapon in the left hand of Nani Wartabone; (4) The weapon in the left hand of Nani Wartabone is a long rifle (hunting rifle) that can be used on the battlefield; (5) The Safari uniform used by Nani Wartabone has patriotic meaning and strength; and (6) Base of 2 and the curve of base of 3 represents the number 23 celebrated as patriotic day by the people of Gorontalo.